A Danger and a Nuisance: Regulating the Automobile in Ontario, 1903-1912 - Los, Christopher (Ontario History)

(untitled) (The Ontario Historical Society, 2014)
In the early twentieth century public opposition to uncontrolled automobile driving pushed successive provincial governments to construct extensive regulatory frameworks around cars. This article will analyze the extensive legislative and common law changes brought about in Ontario from 1903-12 as a window through which to view wider social attitudes towards technology, the state, and government regulation. At first glance restrictions on cars appear to be no more than reactionary measures to appease particular segments of the population. But they can also be seen as a form of opposition to rapid industrialization and the ever-increasing power of technology, and as examples of a growing faith in state power, and a desire to see anti-moral and anti-social behaviour more aggressively policed. Motor vehicle regulation was part of the complex social and political conflicts that characterized progressive-era Ontario.